Epigenetic DNA Methylation Signatures Associated With the Severity of Paget’s Disease of Bone - Diboun, Ilhame; Wani, Sachin; Ralston, Stuart H.; Albagha, Omar M. E. (Frontiers in Cell and Developmental Biology, 2022)
Background: Paget’s disease of bone (PDB) is characterized by focal areas of dysregulated bone turnover resulting in increased bone loss and abnormal bone formation with variable severity. PDB has a complex etiology and both genetics and environmental factors have been implicated. A recent study has identified many differentially methylated loci in PDB compared to healthy subjects. However, associations between DNA methylation profiles and disease severity of PDB have not been investigated. Objectives: To investigate the association between DNA methylation signals and PDB severity. Methods: Using 232 well-characterized PDB subjects from the PRISM trial, a disease severity score was devised based on the clinical features of PDB. DNA methylation profiling was performed using Illumina Infinium HumanMethylation 450K array. Results: We identified 100 CpG methylation sites significantly associated with PDB severity at FDR < 0.05. Additionally, methylation profiles in 11 regions showed Bonferroni-significant association with disease severity including 6 islands (located in VCL, TBX5, CASZ1, ULBP2, NUDT15 and SQSTM1), 2 gene bodies (CXCR6 and DENND1A), and 3 promoter regions (RPL27, LINC00301 and VPS29). Moreover, FDR-significant effects from region analysis implicated genes with genetic variants previously associated with PDB severity, including RIN3 and CSF1. A multivariate predictor model featuring the top severity-associated CpG sites revealed a significant correlation (R=0.71, P = 6.9 x 10-16) between observed and predicted PDB severity scores. On dichotomizing the severity scores into low and high severity, the model featured an area under curve (AUC) of 0.80, a sensitivity of 0.74 and a specificity of 0.68. Conclusion: We identified several CpG methylation markers that are associated with PDB severity in this pioneering study while also highlighting the novel molecular pathways associated with disease progression. Further work is warranted to affirm the suitability of our model to predict the severity of PDB in newly diagnosed patients or patients with family history of PDB.